Organ-specific alternative transcripts of KNOX family class 2 homeobox genes of rice - Ito, Y.; Hirochika, H.; Kurata, N.
We identified three genes (HOS58, HOS59 and HOS66)of rice (Oryza sativa), which encode predicted proteins with the KNOX family class 2 homeodomain. These proteins contain three conserved domains, the KNOX domain, ELK domain and homeodomain, from an N-terminus to a C-terminus. In addition to similarity of predicted amino acid sequences, these genes showed a similar exon/intron structure. cDNA cloning and reverse transcription-polymerase chain reaction analyses of these genes indicated tissue-specific expression of alternative transcripts. The expression of the longer mRNAs of HOS58 (HOS58L)and HOS59L was detected in all organs examined such as roots, leaf blades, leaf sheaths, flowers and calli, whereas the shorter mRNAs of HOS58 (HOS58S)and HOS59S were expressed in leaf blades, leaf sheaths and flowers. The expression of HOS66L was detected in roots, leaf blades, leaf sheaths and flowers, whereas the expression of HOS66S was detected in roots and flowers. The alternative transcripts of HOS66 arose by use of alternative transcription start sites. The longer transcripts contained an exon 1 which encodes an alanine/glycine-rich region, whereas the shorter ones lacked it. These results suggest that the expression of the alternative transcripts is organ-specific, and their products have different degrees of abilities for activation or repression of transcription.
Keywords: TRANSCRIPTION FACTOR; GENOME SEQUENCE